2019
DOI: 10.1097/dss.0000000000002260
|View full text |Cite
|
Sign up to set email alerts
|

Frozen-Section Tissue Processing in Mohs Surgery

Abstract: BACKGROUND Mohs micrographic surgery (MMS) is the most reliable tissue-sparing technique in the management of cutaneous malignancies. Although the concept is simple, there is considerable variability in the mapping and processing techniques used by Mohs surgeons and histotechnicians. OBJECTIVE This review article aims to examine the frozen-section tissue processing techniques. Existing variations will be discussed and pearls offered to optimize the froz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 25 publications
0
24
0
1
Order By: Relevance
“…We noted that thicker tissue specimens, which contained predominantly stiffer connective tissue (nose, lip), had a higher proportion of their surface area in poor contact with the cassette window (3.03% and 4.58%, respectively). Tissue sections rich in collagen are known to be challenging to flatten in frozen section histopathology [ 22 ]. It has been suggested that such tissue specimens are best flattened against a microscope slide to ensure that as much of the tissue margin is found within a single plane as possible [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We noted that thicker tissue specimens, which contained predominantly stiffer connective tissue (nose, lip), had a higher proportion of their surface area in poor contact with the cassette window (3.03% and 4.58%, respectively). Tissue sections rich in collagen are known to be challenging to flatten in frozen section histopathology [ 22 ]. It has been suggested that such tissue specimens are best flattened against a microscope slide to ensure that as much of the tissue margin is found within a single plane as possible [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…While processing of adipose tissue for frozen section histopathology can be challenging due to the lower temperatures needed to freeze such tissue, often resulting in excessive tissue trimming [ 22 ], this tissue type poses no difficulties for the Fast Raman measurements. Adipose tissue is easy to flatten against the cassette window and has very low superficial blood.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, 7 baseline patients' characteristics, recurrence and clinical outcomes were not significantly different between MMS techniques. Comparing both techniques, in terms of performance and implementation in daily practice, frozen MMS (or direct/fresh Mohs) has the main advantage of reducing surgical times as it implies immediate microscopic examination of surgical margins 22,23 and completion of surgery with definite wound closure at the same surgical process 24‐26 …”
Section: Resultsmentioning
confidence: 99%
“…Three-dimensional tissue modeling prior to histological assessment provides smart grossing recommendations while automating the report of tissue size and orientation 66 . We utilized photogrammetry techniques which triangulate image features across multiple viewpoints/images to 3D coordinates in order to generate a 3D model of the tissue.…”
Section: D Tissue Modeling and Grossing Recommendations In 3d Model Panementioning
confidence: 99%